2020
DOI: 10.1093/aobpla/plaa024
|View full text |Cite
|
Sign up to set email alerts
|

Endozoochory of Chrysobalanus icaco (Cocoplum) by Gopherus polyphemus (Gopher Tortoise) facilitates rapid germination and colonization in a suburban nature preserve

Abstract: Some large-seeded plants lack effective seed dispersal agents when they are introduced as ornamental plants to new areas, but can rapidly colonize a landscape if seed dispersal functions are restored. We examined whether Gopherus polyphemus (Gopher Tortoise) facilitated the spread of Chrysobalanus icaco (Cocoplum; Chrysobalanaceae) over a 14-year period in a suburban nature preserve (in Jupiter, FL, USA) by: (i) comparing germination patterns among gut-passed, hand-depulped and whole fruit treatments, and (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…However, more data on these taxonomic groups is needed to determine whether our framework could be applied in these systems. Although some species of frugivorous reptiles and fish are known to disperse seeds (Anderson et al, 2009, 2011; Corlett, 2017; Costa‐Pereira & Galetti, 2015; Hanish et al, 2020; Piazzon et al, 2012; Platt et al, 2013; Valido & Nogales, 1994), the effects of these taxa on seed‐dispersal patterns are notably understudied (Costa‐Pereira & Galetti, 2015; Genes & Dirzo, 2022). Moreover, reptilian social systems can be highly diverse and complex, yet disproportionately understudied compared with other vertebrate taxa (Doody et al, 2013).…”
Section: Social Status Affects the Quantity Of Seeds Dispersedmentioning
confidence: 99%
“…However, more data on these taxonomic groups is needed to determine whether our framework could be applied in these systems. Although some species of frugivorous reptiles and fish are known to disperse seeds (Anderson et al, 2009, 2011; Corlett, 2017; Costa‐Pereira & Galetti, 2015; Hanish et al, 2020; Piazzon et al, 2012; Platt et al, 2013; Valido & Nogales, 1994), the effects of these taxa on seed‐dispersal patterns are notably understudied (Costa‐Pereira & Galetti, 2015; Genes & Dirzo, 2022). Moreover, reptilian social systems can be highly diverse and complex, yet disproportionately understudied compared with other vertebrate taxa (Doody et al, 2013).…”
Section: Social Status Affects the Quantity Of Seeds Dispersedmentioning
confidence: 99%
“…Second, in the primary study only, we tested whether the seeds exposed to gut transit germinated at a greater rate and frequency than those of the controls, viz. the accelerated germination hypothesis (Castilla, 2000;Traveset et al, 2001;Hämäläinen et al, 2017;Hanish et al, 2020;Salazar-Rivera et al, 2020;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The dispersal of many plants depends on transport by seed-dispersing animals [3]. A growing body of research has reported seed dispersal mediated by fish [4], birds [5], primates [6], turtles [7] and lizards [8], which are potential seed dispersers. Lizards can be effective seed dispersers in terms of fruit removal, seed deposition in suitable habitats and seed germination [9].…”
Section: Introductionmentioning
confidence: 99%